Investigation of a Lignin-Based Deep Eutectic Solvent Using p-Hydroxybenzoic Acid for Efficient Woody Biomass Conversion - Wang, Yunxuan; Meng, Xianzhi; Jeong, Keunhong; Li, Shuya; Leem, Gyu; Kim, Kwang Ho; Pu, Yunqiao; Ragauskas, Arthur J.; Yoo, Chang Geun (American Chemical Society, 2020)
Deep eutectic solvents (DESs) are effective solvents for biomass conversion and have been proposed as alternatives to ionic liquids (ILs). Herein, we first report an effective pretreatment of woody biomass using a novel hardwood lignin-based DES prepared from p-hydroxybenzoic acid (PB) and choline chloride (ChCl), which are used as the hydrogen bond donor and acceptor, respectively. The impacts of the ChCl-PB DES on structural properties and enzymatic hydrolysis of poplar wood were comprehensively evaluated. The performance of ChCl-PB DES was also compared with two other DESs with p-coumaric acid (PCA) and 4-hydroxybenzaldehyde (PHA) as the hydrogen bond donors, which have been successfully applied to herbaceous biomass conversion in previous studies. The results showed that hemicellulose and lignin were effectively fractionated during the proposed ChCl-PB DES pretreatment under a relatively mild temperature. The ChCl-PB DES pretreatment resulted in up to 69% of delignification, and the pretreated poplar residues had over 90% of glucose yield by a 72 h-enzymatic hydrolysis. Transformation of poplar biomass during the DES pretreatment was evaluated by gel permeation chromatography (GPC), two-dimensional heteronuclear single quantum coherence (2D-HSQC), and P-31-nuclear magnetic resonance (NMR) spectroscopies. The recovered lignin showed relatively high purity, narrow molecular weight distribution (PDI < 1.6), and relatively low molecular weight (similar to 1400 g/mol for M-w). A sustainable process was achieved by recycling DES as well as the utilization of PB, which is a producible aromatic compound from hardwood lignin, for the proposed DES formation in the system. This study indicates that the proposed novel DES with a hardwood lignin-based PB compound is a promising pretreatment solvent to achieve an economically feasible biomass conversion process.
Keywords: LIGNOCELLULOSIC BIOMASS; IONIC LIQUIDS; CHOLINE CHLORIDE; PRETREATMENT; RECALCITRANCE; NMR; VARIANTS; RESIDUES; BIOFUELS; POPLAR